2014
DOI: 10.4161/21624011.2014.953407
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic cyclophosphamide enhances HPV16E7 peptide vaccine induced antigen-specific and cytotoxic T-cell mediated antitumor immune response

Abstract: In clinical trials, metronomic cyclophosphamide (CPA) is increasingly being combined with vaccines to reduce tumor-induced immune suppression. Previous strategies to modulate the immune system during vaccination have involved continuous administration of low dose chemotherapy, studies that have posed unique considerations for clinical trial design. Here, we evaluated metronomic CPA in combination with a peptide vaccine targeting HPV16E7 in an HPV16-induced tumor model, focusing on the cytotoxic T-cell response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 44 publications
3
57
0
Order By: Relevance
“…As expected, we found that there were strong antigen-specific immune cell responses in both the spleen and RLN at both time points for the DPX-R9F and w/o-R9F treated groups. Peak immune responses were detected in the spleen and RLN on day 7, which typically corresponds to peak immune responses induced by vaccination [43]. At this time, antigen-specific immune response could also be detected in the LLN, but these responses declined significantly by day 14, especially for the DPX-R9F group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, we found that there were strong antigen-specific immune cell responses in both the spleen and RLN at both time points for the DPX-R9F and w/o-R9F treated groups. Peak immune responses were detected in the spleen and RLN on day 7, which typically corresponds to peak immune responses induced by vaccination [43]. At this time, antigen-specific immune response could also be detected in the LLN, but these responses declined significantly by day 14, especially for the DPX-R9F group.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines were prepared either as a proprietary DPX formulation [37, 43] or using a water-in-oil (w/o) emulsion [48]. For DPX with R9F, lipid-mixture containing phosphotidyl choline and cholesterol in a 10:1 ratio (w:w) (Lipoid GmBH, Germany), R9F (5 μg/dose), F21E (5 μg/dose), and a proprietary polynucleotide based adjuvant (20 μg/dose) were formulated in 40% tert-butanol, freeze-dried and resuspended in Montanide ISA51 VG (SEPPIC, France).…”
Section: Methodsmentioning
confidence: 99%
“…Metronomic dosing schedules aim to achieve adequate disease control with less toxicity than MTD chemotherapy. The rationale for LDM is to not only inhibit tumor growth but also induce ICD and anti-tumor immune responses [47] to make patients highly responsive to immunotherapies. A LDM chemotherapy can control tumor progression in patients with early stage as well as those with advanced-stage cancers [8].…”
Section: Low Dose Metronomic (Ldm) Chemotherapy For An Effective Imentioning
confidence: 99%
“…In fact, the anti-tumor efficacy of doxorubicin has been suggested to depend on the host immune system [46] such that depletion of T cells compromises anti-tumor efficacy of doxorubicin [47]. LDM chemotherapy also has been shown to be a suitable preparative regimen for vaccination approach in order to boost anti-tumor immune responses against dormant cells [7]. Similarly, whereas fractionated radiation therapy (RT) is immunogenic and generates abscopal responses in mice, single high-dose RT fails to do so [48].…”
Section: Low Dose Metronomic (Ldm) Chemotherapy For An Effective Imentioning
confidence: 99%
“…161,162 Moreover, the clinical profile of Imlygic Ò combined with the FDA-approved cytotoxic T lymphocyte-associated 4 (CTLA4)-targeting monoclonal antibody ipilimumab 163,164 has been assessed in 18 patients with unresectable Stage IIIB-IV melanoma (NCT01740297). 165 Reolysin Ò (a proprietary variant of reovirus serotype 3 -Dearing strain) 166 has been tested either as standalone immunotherapeutic agent in 12 myeloma patients and in 15 subjects with recurrent malignant gliomas, 167,168 or combined with low-dose cyclophosphamide 169,170 in 29 children with relapsed or refractory extra-cranial solid tumors (NCT01240538), 171 and in 36 individuals affected by advanced neoplasms. 172 The safety and efficacy of Cavatak TM (a proprietary variant of Coxsackievirus A21) 173 administered intratumorally or intravenously as standalone immunotherapeutic agent have been evaluated in 57 subjects with unresectable Stage IIIC-IV melanoma (NCT01227551), 174,175 and in 30 individuals with other advanced solid malignancies (NCT02043665).…”
Section: Completed Clinical Studiesmentioning
confidence: 99%